Subjective Academic Achievement, Economic Status, and Smoking and Drinking Behaviors among Adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study aimed to examine the relationship between subjective academic achievement, economic status, and smoking and drinking behaviors among adolescents in one region of South Korea. In this study, a secondary analysis was performed on data of adolescents in 2020. The present study found that smokers had lower subjective academic scores than nonsmokers (t=15.343, p<0.001), and drinkers had lower subjective academic scores than nonsmokers (t=8.821, p<0.001). In terms of subjective economic status, smokers had lower subjective economic status scores than nonsmokers (t=7.378, p=0.003), and drinkers had lower subjective economic status scores than nonsmokers (t=6.080, p=0.001). Efforts should be made to increase academic achievement by preventing smoking and drinking behaviors in adolescents. Therefore, it is necessary to prevent an increase in exposure to smoking and drinking owing to socioeconomic status.